Filopodia Formation in the Absence of Functional WAVE- and Arp2/3-Complexes - Steffen, Anika (The American Society for Cell Biology, 2006)
Cell migration is initiated by plasma membrane protrusions, in the form of lamellipodia and filopodia. The latter rod-like projections may exert sensory functions and are found in organisms as distant in evolution as mammals and amoeba such as Dictyostelium discoideum. In mammals, lamellipodia protrusion downstream of the small GTPase Rac1 requires a multimeric protein assembly, the WAVE-complex, which activates Arp2/3-mediated actin filament nucleation and actin network assembly. A current model of filopodia formation postulates that these structures arise from a dendritic network of lamellipodial actin filaments by selective elongation and bundling. Here, we have analyzed filopodia formation in mammalian cells abrogated in expression of essential components of the lamellipodial actin polymerization machinery. Cells depleted of the WAVE-complex component Nck-associated protein 1 (Nap1), and, in consequence, of lamellipodia, exhibited normal filopodia protrusion. Likewise, the Arp2/3-complex, which is essential for lamellipodia protrusion, is dispensable for filopodia formation. Moreover, genetic disruption of nap1 or the WAVE-orthologue suppressor of cAMP receptor (scar) in Dictyostelium was also ineffective in preventing filopodia protrusion. These data suggest that the molecular mechanism of filopodia formation is conserved throughout evolution from Dictyostelium to mammals and show that lamellipodia and filopodia formation are functionally separable.